The Amateur Basketball Team of the Multinational Company Ernst Young in Belgrade as a Folklore Group - Bogdan Dražeta (University of Belgrade, 2021)
The subject of the analysis of our paper is the social and cultural practice of amateur basketball played by employees of the multinational company Ernst Young in Belgrade. We observed the amateur team as a folklore group, and their participation in sports is interpreted not only as a physical activity, but as a modality of shaping attitudes, values and beliefs related to the company, important for strengthening cohesion among employees and reinforcing their motivation to perform work tasks. Basketball as a sport in which each player aligns on an individual level with the collective strategy of the team is somewhat reminiscent of the activities of Ernst Young employees, such as teamwork, personal and professional development, as well as an organizational culture oriented towards the company’s development and growth on the market. The material in this paper was collected using the technique of semi-structured interviews with members of the amateur basketball team Ernst Young, which competes in the Rekreativ League of Belgrade and is composed mainly of employees in this organization. In addition to this base of our ethnographic material, informal interviews were conducted and employee statementsobtained. Using the concept of idioculture of the American sociologist, social psychologist and folklorist Gary Alan Fine, the material related to the creation, expression and subsistence of the group’s identity (composed mostly of amateur basketball players) was analyzed and interpreted. Members of this sports community differentiate themselves from other employees in the multinational company through the mentioned group identity. The group is recognized as such by other employees in this organization, which was shown by further analysis performed in accordance with the theoretical and methodological framework of the “folklore diamond” established by Gary Alan Fine. However, Fine himself never applied this framework consistently according to all its elements of analysis. The selection of these elements is made with regard to what is being examined, hence Fine’s “folklore diamond” is used as a source from which analytical concepts are taken and combined. The cultural context, as another element, gives a more complete picture of the overall analysis. This gives us an impetus for further ethnological and anthropological research of amateur sports in Serbia, especially in the corporate work environment.